2024
DOI: 10.1021/acs.langmuir.3c03742
|View full text |Cite
|
Sign up to set email alerts
|

Self-Catalyzed Synthesis of Length-Controlled One-Dimensional Nickel Oxide@N-Doped Porous Carbon Nanostructures from Metal Ion Modified Nitrogen Heterocycles for Efficient Lithium Storage

Ming Chen,
Ming-Yang Zhao,
Feng-Ming Liu
et al.

Abstract: Transition metal oxides with the merits of high theoretical capacities, natural abundance, low cost, and environmental benignity have been regarded as a promising anodic material for lithium ion batteries (LIBs). However, the severe volume expansion upon cycling and poor conductivity limit their cycling stability and rate capability. To address this issue, NiO embedded and N-doped porous carbon nanorods (NiO@NCNR) and nanotubes (NiO@NCNT) are synthesized by the metalcatalyzed graphitization and nitridization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition to its role as a catalyst in the CVD growth of graphene, Mo 2 C has been considered a candidate material for energy storage device applications. First-principles calculations predict a very fast diffusion of Li, Na, and K ions on intrinsically stable, metallic Mo 2 C. , Studies have shown that monolayer Mo 2 C as well as composite structures comprising of Mo 2 C and carbon nanomaterials (carbon nanotubes, graphene, reduced graphene oxide, and porous carbon) can be used as a promising anode material for Li-ion batteries. , However, repeated electrochemical reactions cause the accretion of Mo 2 C particles, which decreases the active sites and hence results in poor cyclability and rapid capacity fading . As a solution to this issue, different strategies, such as the design of hybrid materials, carbon composition, nanostructuring, etc., have been implemented. , Embedding Mo 2 C into graphene layers can be considered an attractive strategy because this hybrid material can perform as a superior anode material with enhanced cyclability, Li + storage performance, surface area, electrical conductivity, chemical stability, and structural flexibility. , Recent studies have also demonstrated the enhanced electrochemical performance of various other composite anode and cathode materials, where metal oxides such as NiO, Co 3 O 4 , and LiFePO 4 have been wrapped with carbon-based nanostructures such as N-doped carbon nanoribbons and nanotubes, graphitic carbon nanotubes, porous nanocarbon, and so on. In these composite or hybrid anodes, carbon materials serve as excellent coating layers, significantly improving the overall electrode performance and stability. While there are a few reports on the application of graphene/Mo 2 C hybrid nanostructures as an anode material for lithium-ion batteries, the exploitation of such hybrid material in thin film form for micro battery applications remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role as a catalyst in the CVD growth of graphene, Mo 2 C has been considered a candidate material for energy storage device applications. First-principles calculations predict a very fast diffusion of Li, Na, and K ions on intrinsically stable, metallic Mo 2 C. , Studies have shown that monolayer Mo 2 C as well as composite structures comprising of Mo 2 C and carbon nanomaterials (carbon nanotubes, graphene, reduced graphene oxide, and porous carbon) can be used as a promising anode material for Li-ion batteries. , However, repeated electrochemical reactions cause the accretion of Mo 2 C particles, which decreases the active sites and hence results in poor cyclability and rapid capacity fading . As a solution to this issue, different strategies, such as the design of hybrid materials, carbon composition, nanostructuring, etc., have been implemented. , Embedding Mo 2 C into graphene layers can be considered an attractive strategy because this hybrid material can perform as a superior anode material with enhanced cyclability, Li + storage performance, surface area, electrical conductivity, chemical stability, and structural flexibility. , Recent studies have also demonstrated the enhanced electrochemical performance of various other composite anode and cathode materials, where metal oxides such as NiO, Co 3 O 4 , and LiFePO 4 have been wrapped with carbon-based nanostructures such as N-doped carbon nanoribbons and nanotubes, graphitic carbon nanotubes, porous nanocarbon, and so on. In these composite or hybrid anodes, carbon materials serve as excellent coating layers, significantly improving the overall electrode performance and stability. While there are a few reports on the application of graphene/Mo 2 C hybrid nanostructures as an anode material for lithium-ion batteries, the exploitation of such hybrid material in thin film form for micro battery applications remains elusive.…”
Section: Introductionmentioning
confidence: 99%